Taking up the ordinary from the philosophy of language: Review of: Pérez Chico, D. (ed.) (2023). Cuestiones de la filosofía del lenguaje ordinario. Zaragoza: Prensas de la Universidad de Zaragoza. - Vera Vega, Pablo (Analysis. Journal of Philosophical Research, 2023)
Review of: Pérez Chico, D. (ed.) (2023). Cuestiones de la filosofía del lenguaje ordinario. Zaragoza: Prensas de la Universidad de Zaragoza.